EFFECTS OF ADDING ZEOLITE TO THE RATION ON THE PRODUCTION PERFORMANCE OF MICE (MUS MUSCULUS): THE FIRST AND THE SECOND OF LITTER SIZE - Kartiarso Kartiarso; Pollung H. Siagian; R. Panda; U. D. Octaviana (Institut Teknologi Bandung, 2007)
The research has been conducted to study the effect of adding zeolite to the ration on the production performance of mice (Mus musculus). The litter of the first (LS12) and second (LS2) from the same mice which received rations added with zeolite for a long period of time were used in this experiment. The rations with different level of zeolite ( 0,3, 6 and 9%) were used for male and female experimental mice from LS1 and LS2. Randomized Complete Design (RCD) with two factors, namely level of zeolite and sex, with six replication used in this experiment. The result showed that added zeolite to the ration did not affect feed consumption but significantly increased body weight gain and feed efficiency, reduced water and protein content of feces but significantly increased protein digestibility. Mortality rate in this experiment was very low ( 1.6